Risk assessment of the chiral pesticide fenamiphos in a human model: Cytochrome P450 phenotyping and inhibition studies - de Albuquerque, Nayara Cristina Perez; Carrão, Daniel Blascke; Habenschus, Maísa Daniela; Fonseca, Franciele Saraiva; Moreira da Silva, Rodrigo; Lopes, Norberto Peporine; Rocha, Bruno Alves; Barbosa Júnior, Fernando; de Oliveira, Anderson Rodrigo Moraes [UNESP] (My University, 2020)
Fenamiphos (FS) is a chiral organophosphate pesticide that is used to control nematodes in several crops. Enantioselective differences may be observed in FS activity, bioaccumulation, metabolism, and toxicity. Humans may be exposed to FS through occupational and chronic (food, water, and environmental) exposure. FS may cause undesirable CYP450 pesticide-drug interactions, which may impact human health. Here, the CYP450 isoforms involved in enantioselective FS metabolism were identified, and CYP450 inhibition by rac-FS, (+)-FS, and (−)-FS was evaluated to obtain reliable information on enantioselective FS risk assessment in humans. CYP3A4 and CYP2E1 metabolized FS enantiomers, and CYP2B6 may participate in rac-FS metabolism. In addition, rac-FS, (+)-FS, and (−)-FS were reversible competitive CYP1A2, CYP2C19, and CYP3A4/5 inhibitors. High stereoselective inhibition potential was verified; rac-FS and (−)-FS strongly inhibited and (+)-FS moderately inhibited CYP1A2. Stereoselective differences were also detected for CYP2C19 and CYP3A4/5, which were strongly inhibited by rac-FS, (+)-FS, and (−)-FS. Our results indicated a high potential for CYP450 drug-pesticide interactions, which may affect human health. The lack of stereoselective research on the effect of chiral pesticides on the activity of CYP450 isoforms highlights the importance of assessing the risks of such pesticides in humans.
Keywords: CYP450; Fenamiphos; Human microsomes; In vitro; Inhibition; Phenotyping